EXPLORING SEMANTIC ENTAILMENT STRATEGIES OF THE MAIN CHARACTERS IN "SET IT UP" - Rizka Aulia Tambunan; Erika Sinambela; Rosdiana Rajagukguk (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study examined semantic entailment in the dialogues of the main characters in the movie Set It Up (2018). The research aimed to identify the types of entailment used and determine the most dominant type in the film. A descriptive qualitative method was applied, focusing on textual analysis of spoken utterances produced by the main characters, Harper Moore and Charlie Young. The data were collected through visual analysis and note-taking techniques, including watching the movie, transcribing dialogues, and selecting relevant utterances containing entailment. The findings revealed that four types of entailment were identified, namely one-way entailment, two-way entailment, negative entailment, and metaphorical entailment. A total of 30 data were analyzed, showing that one-way entailment was the most dominant type, followed by negative entailment, two-way entailment, and metaphorical entailment. The results indicated that entailment played an important role in constructing meaning, expressing intentions, and creating humor in the dialogues. In conclusion, semantic entailment contributed significantly to meaning-making in film discourse, particularly in reflecting interpersonal relationships and communicative strategies within a workplace setting.